A Strong Hybrid S-Box Scheme Based on Chaos, 2D Cellular Automata and Algebraic Structure - Amirul Haque; Tabarak Ali Abdulhussein; Musheer Ahmad; Mayadah Waheed Falah; Ahmed A. Abd El-Latif (IEEE Access)
Substitution-boxes are the main deciding components in symmetric-key cryptosystems for resisting many cryptanalytic attacks. It has been a challenging task for the designers to construct strong S-box which satisfies multiple cryptographic properties simultaneously. A number of S-box studies have been investigated in literature; but, the generated S-box found to exhibit one single property with good score. This paper proposes a novel creation of S-boxes which possess excellent scores of multiple cryptographic properties instead of only one property. The suggested hybrid S-box method explores the science of two-dimensional cellular automata theory, discrete chaotic maps, and algebraic group structure. The proposed anticipated $8× 8$ S-box holds excellent security performance features such as: minimum nonlinearity as high as 110, no fixed points, satisfaction of strict avalanche and bits independence criterions, differential uniformity as low as 6, linear approximation probability as low as 0.0703, and auto-correlation function (absolute indicator) of 40. The performance comparison indicates the proposed S-box has superior features, greater inherent security and robustness strength than many available state of the art S-box methods.